2021
DOI: 10.21037/tp-20-178
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of PEG-asparaginase versus E. coli L-asparaginase in Chinese children with acute lymphoblastic leukemia: a meta-analysis

Abstract: Background: Multiagent chemotherapy is the primary treatment for acute lymphoblastic leukemia (ALL), of which asparaginases including Escherichia coli L-asparaginase (E. coli L-Asp) and pegylated-asparaginase (PEG-Asp), are cornerstone components. The study aimed to conduct a meta-analysis to compare the efficacy and safety of PEG-Asp with E. coli L-Asp in Chinese children with ALL. Methods: A systematic literature search was conducted to collect randomized controlled trials (RCTs) on PEG-Asp versus E. coli L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
0
7
0
6
Order By: Relevance
“…Additionally, the use of PEG Asparaginase in pharmacotherapy may lessen the financial burden associated with using medical resources because of decreased administration frequency and a shorter length of hospital stay. 12…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the use of PEG Asparaginase in pharmacotherapy may lessen the financial burden associated with using medical resources because of decreased administration frequency and a shorter length of hospital stay. 12…”
Section: Discussionmentioning
confidence: 99%
“…These two trials contributed to an expanded approval for pegaspargase in 2006 for the firstline treatment of patients with ALL (20). More recently several large systemic reviews have reinforced these early findings and demonstrated superiority of pegaspargase in comparison to native E. coli asparaginase (23)(24)(25). Cost effectiveness of pegaspargase in comparison to native E. coli asparaginase has also been demonstrated (26).…”
Section: Currently Available Productsmentioning
confidence: 98%
“…Terdapat beberapa kekurangan pada studi metaanalisis oleh Dai dkk. 10 Pertama, studi yang dimasukkan semua dipublikasi di China dengan skala kecil. Kedua, penilaian risiko bias menggunakan Cohrane recommendation tool menunjukkan adanya 3/15 studi dengan risiko bias yang tinggi terkait kurangnya informasi mengenai metode yang digunakan.…”
Section: Hasil Penelusuran Literaturunclassified
“…Dengan frekuensi penyuntikan yang lebih sedikit maka angka kunjungan ke rumah sakit berkurang dan dapat mengurangi beban biaya kesehatan. 10 Pada studi Dai dkk, 10 kelompok yang mendapat PEG-asp secara bermakna menunjukkan frekuensi kunjungan ke RS lebih sedikit dan lama masa perawatan lebih rendah (p<0,00001). Suatu studi yang menilai costeffectiveness PEG-asp dibandingkan L-asp di Inggris mendapatkan bahwa PEG-asp sebagai multi-agen kemoterapi pada anak dengan LLA lebih efisien.…”
Section: Ikatan Tersebut Dapat Menjaga Aktivitas Enzim Danunclassified